An Interactive Mobile Apps for Kolej Teratai Students / Rahimi Roslan - Roslan, Rahimi (2020)
Kolej Kediaman Teratai is the second one of the college in UiTM that has a lot of activity that they want to do for the college student. However, some of the activity will be do mostly once a week. For examples, religious study, usrah, food business and barber corner. The main problem is the notices of college activity are not conveyed properly. Hence, the objective of this project is to design an interactive system that deliver information to the student by providing the develop the mobile application that specifully give info activities held in college. Furthermore, this system was test an interactive information system functional, reliables and usables for college student. For this project, the agile method was apply because this method was usually been use by any other company to develop the system. For examples, planning, analysis, design, implementation, testing and maintenance was used in developing the system. This project was build a mobile application. The testing process was done frequently and repeated by check for error, bug and interoperability before the application is published or made public. An interfaces, code writing, compile and testing was done develop using Java language. The data from this application was store using Firebase database.